EXTENSIVELY DRUG RESISTANT (XDR) SALMONELLA TYPHI RED FLAG FOR CLINICIANS AT KARACHI - Bakhat, Shaista; Nadeem, Saman; Hussain, Ashfaq; Sarwar, Saba; Hussain, Beenish; Faheem, Faisal (Infectious Diseases Journal of Pakistan, 2023)
Background: Salmonella typhi cause enteric fever which is a grave community health problem with increasing antibiotic resistance. Salmonella typhi is responsible for 10.9 million morbidities and 116800 mortalities worldwide with the greatest burden falling on third world countries. It is common among children with incidence rate of typhoid fever 573.2 per 100,000 in aged 2-5years and 451.7 cases per 100,000 children per year among 2-15years old in Pakistan. Early detection of Salmonella typhi and selection of appropriate antibiotics are important to mitigate the morbidity and fatality rate related to these kinds of infections. We have conducted this study to assess the extensively drug resistance in isolates of Salmonella typhi in Karachi, Pakistan. Material and Methods: This cross-sectional study was done at private set up, Karachi from 2019-2021. This study was ethically approved from hospital management. Data related to phenotypic detection of antimicrobial susceptibility was obtained from LIMS (Laboratory Information Management System). According to record both in-door and out-door patients were included in the study. The collected data was scrutinized by using descriptive statistics performed with SPSS version 24. Chi-square was used to test for statistical significance (P ≤ 0.05). Results: Total 10564 samples were extracted from data, out of which 4582 samples were found positive for growth of different microorganisms. Salmonella typhi were positive in 1500 cases and only 412 samples were exhibiting XDR Salmonella typhi. Maximum cases of XDR Salmonella typhi were detected in age group 5-10 years with 38.8%. There were 61% male and 39% female. Conclusion: Our study explains that cases of enteric fever as a result of Salmonella typhi are swarming in all cities of Pakistan and particularly at Karachi. XDR is not restricted to Karachi but it is the tip of the iceberg. There is an urgent need to detect these cases timely and start appropriate treatment to overcome complications. Keywords: Salmonella typhi, XDR, Antimicrobial susceptibility, Ceftriaxone, Azithromycin.